Tjäna pengar som gräs? - Svedberg, Martin (2005)
The producers of grain in Sweden are facing a rough future. The competition is getting harder all the time, in Sweden, in EU and also from the "world market". The producers have to be more efficient and have to have bigger units. Many producers might have to look for new alternative production opportunities. In this examstudies I have chosen to investigate the production of lawn. I think lawn could be an alternative to grain production. Production of lawn do not need as big area and it is a more extensive production that gain bigger profit compared to grain. In this study I have investigated how to produce lawn. Some of my issues where: what kind of machinery do I need, what is the best kind of soil and how to harvest it. I have also made a calculation that includes costs and profits. For my research I have used two companies (Skånefrö AB and Weibulls AB), different kind of brochures and a year book from Maskinringen. The calculations shows that it can give a lot of money when producing lawn, but the investments to start producing are big. The production is very sensitive for changing in the market, and there is right now no need fore more producers. When starting a lawn production you have to be careful and consider the fast changes in the market.